2020
DOI: 10.1002/pc.25679
|View full text |Cite
|
Sign up to set email alerts
|

Catechol‐based co‐deposited carbon fiber surfaces for enhancement of fiber/epoxy composites

Abstract: To improve interfacial adhesion between carbon fiber (CF) and epoxy resin, a low‐cost and environment‐friendly method was developed to treat the CF surface via the bio‐inspired co‐deposition of catechol (Cc) and polyethyleneimine (PEI). It is noteworthy that the deposition process reacts at room temperature with water as solvent, and does not require harsh conditions or the use of toxic reagents. After treatment, the CF/epoxy composites were endowed with excellent mechanical properties and showed increases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The N1s subpeaks at 397.96, 399.77, and 401.30 eV ascribed to -NH 2 , -NH-, and -N═, respectively. [41] These results demonstrated that the formation process of this laser-triggered PDA coating went through oxidation and nucleophilic reaction, along with Michael addition and Schiff base reaction, which agreed with the typical base-induced PDA coating. Further, we tested the time-dependent behavior of N1s.…”
Section: Resultssupporting
confidence: 77%
“…The N1s subpeaks at 397.96, 399.77, and 401.30 eV ascribed to -NH 2 , -NH-, and -N═, respectively. [41] These results demonstrated that the formation process of this laser-triggered PDA coating went through oxidation and nucleophilic reaction, along with Michael addition and Schiff base reaction, which agreed with the typical base-induced PDA coating. Further, we tested the time-dependent behavior of N1s.…”
Section: Resultssupporting
confidence: 77%
“…Figure S2 shows that XRD pattern consisted of a broad diffraction peak at 20.72° without any detectable sharp peaks, which indicates the amorphous molecular structure of samples. As is shown in Figure 3 b, a new signal, N1s at 400.1 eV, [ 41 , 42 , 43 ] appears in the spectra of CC-PEI@CNFs, and N1s accounts for 3.35% of CPC-2. Figure 3 c shows three broad peaks at around 280, 322, and 480 nm in the solution, which is suggested as evidence for the cross-linking reaction [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 83%
“…As is shown in Figure 3 b, a new signal, N1s at 400.1 eV, [ 41 , 42 , 43 ] appears in the spectra of CC-PEI@CNFs, and N1s accounts for 3.35% of CPC-2. Figure 3 c shows three broad peaks at around 280, 322, and 480 nm in the solution, which is suggested as evidence for the cross-linking reaction [ 41 , 42 ]. Figure S3 shows the N1s pattern of CNFs and CC-PEI@CNFs, and XPS N1s spectrum of CC-PEI@CNFs can be curve-fitted with three peak components at a binding energy of 398.6, 399.9, and 401.4 eV, which correspond to –NH 2 , –R 2 NH, and –N=, [ 43 , 44 ] respectively.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The surface structures of different fibers were further confirmed by Raman measurements. As shown in Figure 4b, two typical peaks at 1350–1360 cm –1 and 1590–1600 cm –1 correspond to the D‐band and G‐band, [ 27 ] and their intensity ratio ( I D / I G ) is often used to indicate the structural disorder of carbonaceous materials. [ 25 ] In addition, the peak at 575 cm –1 was caused by the stretching vibration of MnO, and the Raman band at 647 cm –1 belonged to the symmetrical stretching vibration of MnO.…”
Section: Resultsmentioning
confidence: 99%